Improved electrochemical performance of boron-doped carbon-coated lithium titanate as an anode material for sodium-ion batteries. Issue 6 (20th January 2017) - Yun, Bin-Na; Du, Hoang Long; Hwang, Jang-Yeon; Jung, Hun-Gi; Sun, Yang-Kook
Abstract : A boron-doped carbon layer (BC) was coated on porous micron-sized Li4 Ti5 O12 (LTO) via a facile wet-chemical method for use as a promising anode material for sodium-ion batteries. Abstract : A boron-doped carbon layer (BC) was coated on porous micron-sized Li4 Ti5 O12 (LTO) via a facile wet-chemical method for use as a promising anode material for sodium-ion batteries. As determined by X-ray photoemission spectroscopy and Raman spectroscopy, three different species (BC3, BC2 O, and BCO2 ) were doped in the carbon layer on the surface of LTO. These heteroatoms lead to abundant extrinsic defects in the carbon layer that result in improved Na-ion diffusivity across the active material. Using electrochemical impedance spectroscopy, the diffusion coefficient of the boron-doped carbon-coated LTO (BC-LTO) was found to be 2.241 × 10 −15 cm 2 s −1 . The BC-LTO exhibited 85% and 60% higher Na-ion diffusivity than pristine LTO and carbon-coated LTO (C-LTO), respectively. Moreover, electron-deficient boron in BC3 enhances the electric conductivity through positively charged holes that carry electrons through the carbon structure. Accordingly, the BC-LTO electrode showed a high specific capacity of 148 mA h g −1 at 0.5C and 98.4 mA h g −1 at 10C rate. In addition, the BC-LTO anode demonstrated a great capacity retention of about 90% at 1 and 10C after 300 cycles. These findings demonstrate the promising potential of LTO as a high-performance anode material for sodium-ion batteries.